Factoring in Desirability American Ballet Theatre at City Center - Jowitt, Deborah 1934- (Dance Books Ltd., Alton,Hampshire (UK), 2005)
American Ballet Theatre at City Center. ABT's men affect New Yorkers the way Nijinsky enthralled Parisians. PALABRAS CLAVE: American Ballet Theatre.